Kepastian Hukum Bagi Pelaku Bisnis Dalam Memperoleh Izin Berusaha Melalui Lembaga Perizinan Online Single Submission (OSS) - Mayasari, Dita Nur (Media Hukum Indonesia (MHI), 2025)
Providing legal certainty is a crucial aspect in creating a conducive investment climate for business actors. One of the Indonesian government's efforts to realize this is through the implementation of an integrated electronic-based business licensing system, namely the Online Single Submission (OSS). This study aims to analyze the extent to which the OSS system is able to provide legal certainty for business actors in obtaining business licenses. The method used is normative juridical with a statutory regulatory approach and literature studies on various related regulations, such as the Job Creation Law and its implementing regulations. The results of the study show that although OSS provides easy access and efficiency of the licensing process, there are still a number of obstacles that affect legal certainty, such as data inconsistency between institutions, sudden changes in regulations, and limited understanding of business actors regarding the OSS system. Therefore, it is necessary to improve the system, increase coordination between institutions, and provide ongoing legal counseling in order to realize a transparent, accountable, and efficient licensing system.